The Indonesian Subtitles of Qiqi and Bennett Characters’ Utterances in Genshin Impact Game: A Study of Subtitling Strategies - Ivan Chandra Nova; Harris Hermansyah Setiajid (Universitas Muhammadiyah Semarang, 2022)
Video game translation is a complex process that uses many aspects from other types of translation, such as literary translation, subtitling strategy, and audiovisual translation into a dynamic whole. Video game presents as a new medium in translation study. Even though video games translation is a new thing in translation study, the translation practice has been done many times over the past last year.This study will do research on a Game named “Genshin Impact”. The characters were chosen because both of them have different characteristics and behaviour in the game. Moreover, both of these characters come from a different town that has a different culture which leads to differences in their utterances. Therefore, both characters have different kinds of utterances which will be interesting to trace how the subtitlers apply the strategies for each character’s utterances.This research aims at analysing the subtitling strategy employed to translate the Qiqi and Bennett utterances, from English to Indonesian. All utterances of both characters will be analysed in this research. English will be the source language and Indonesian will be the target language as the data for this research. There are many strategies found which are used to translate both characters’ utterances, such as condensation, imitation, and transfer. It is expected that the research will find a result which might contribute to the game subtitlers.